Gestão dos bens permanentes e seus resíduos em uma prefeitura no Sul do Estado de Minas Gerais - Silva , Joyce Vanuele (2022)
Brazil is one of the countries that produces the most solid waste, along with this growth, we can still see the expressive changes in its characteristics and the expansion of its dangers. To mitigate this scenario, the National Solid Waste Policy was implemented, bringing a set of actions aimed at finding solutions for solid waste. Municipalities are responsible for preventing waste from being disposed of irregularly and are responsible for developing methods related to non-generation or reduction of waste. The importance of efficient permanent public goods waste management within any public sector brings with it improvements and success in the provision of services offered to users of the public property sector as well as the entire community. The organization under study is a city hall located in a city in the southern region of the state of Minas Gerais. The issues addressed in this work refer to the process of functioning of the heritage sector of the city studied, with a view to understanding the management of solid waste from permanent goods and analyzing whether the final destination of permanent public goods is in accordance with the National Solid Waste Policy. To support this work, a theoretical framework was built that addressed the following themes: Solid Waste, National Solid Waste Policy, Public Heritage, Public Heritage Administration, Public Property Registration and Public Property Control. To this end, the research used the case study method, in order to portray the functioning process of public heritage management, understand the management of solid waste from permanent goods and analyze whether the final destination of permanent public goods is in accordance with agreement National Policy Solid Waste. Data were collected through guided interviews with employees of the heritage sector and with servers that use the servers provided by the sector, guided by an interview script. Through the research, it was possible to perceive the difficulties faced, namely: the lack of communication between the sectors involved, the turnover of employees, the lack of training and the absence of control and monitoring of the existing assets in the municipality, the lack of a permanent public assets management plan and the final destination of permanent assets that do not meet the requirements of the PNRS. In this way, possibilities for improvements were proposed to have a more efficient asset management, through the creation of an internal regulation, appointment of an asset agent for each sector, constitution of a commission to organize inventory and implement training for servers to use the operating system. correctly, elaborating methods that could guide those involved in this theme and carrying out theoretical and practical training to understand the PNRS. Finally, it is expected that the research can provide subsidies for the proposition of new studies in this area, both in the city studied itself, and in other municipalities in relation to the understanding and relevance of maintaining efficient control over the management of waste from public goods permanent.